The determination of whether a Unified Communication System can be effective in supporting informal communication and collaboration in virtual teams - Hill, Kyle (Rhodes University, Faculty of Commerce, Department of Information Systems, 2020)
The overall objective of the research is to determine whether a Unified Communication System intervention can be effective in supporting informal communication and collaboration in virtual teams. In so doing, this research is aimed at developing a current framework of critical success factors for facilitating informal collaboration and communication. As teams have evolved to the point where there is no longer a need for team members to be co-located, with a greater importance now being placed on how they collaborate, this framework will also highlight how it can support virtual teams due to the huge potential advantage they can provide to the organisation. A virtual communication and collaboration system will be selected based on the outputs of the current framework and interactions which occur through the system will be observed to provide quantitative and qualitative results. In conclusion, the research will suggest recommendations for the successful implementation of informal communication and collaboration technologies within the organisation. The research will also indicate to a limited degree, the impact of the implementation of these technologies, and the outcome for the organisation, whether positive or negative. Whilst conducting the research, it became apparent that while the UCS was capable of performing the processes and functions required, the individuals and teams engaging with the technology did not always make use of the full scope of the technology provided. Regardless, a UCS was observed to provide direct benefits to an organisation in increasing communication and collaboration in the organisation. These increases can be observed in both the physical and virtual sense. However, the converse is true for generating social capital which lead to the observation that there are a smaller number of interactions happening in the smaller teams, but these are of higher value when compared to the larger teams of this study. It is also clear that the larger a team becomes, the more the trend is to focus on adopting new technologies to make their roles more efficient. This adoption is not however translated into outputs such as social capital but is translated into stronger networks and the formation of new networks. It is also clear that most negative factors around the UCS are related to the respondent's hardware rather than the solution itself. Cost reductions because of virtuality will also be observed and using the Developed Framework as a blue print, an organisation should be able to observe direct benefits for an organisation by being able to confirm the thesis of this research in that having a UCS intervention is effective in supporting informal communication and collaboration in virtual teams.
Keywords: Telecommuting; Virtual work teams; Telecommunication systems; Computer networks